1991
DOI: 10.1111/j.1432-1033.1991.tb16459.x
|View full text |Cite
|
Sign up to set email alerts
|

Base 2661 in Escherichia coli 23S rRNA influences the binding of elongation factor Tu during protein synthesis in vivo

Abstract: The binding of the EF-Tu . GTP . aminoacyl-tRNA ternary complex (EF, elongation factor) to the ribosome is known to be strengthened by a 2661G-to-C mutation in 23s ribosomal RNA, whereas the binding to normal ribosomes is weakened if the factor is in an appropriate mutant form (Aa). In this report we describe the mutual effects by the 2661C alteration in 23s rRNA and EF-Tu(Aa) on bacterial viability and translation efficiency in strains with normal or mutationally altered ribosomes. The rrnB(2661C) allele on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Further, the G2661C/S12-SmP double mutant can be rescued not only by Smmediated reinforcement at the shoulder, but also by certain kirromycin-resistant (KirrR) mutants of EF-Tu (173). These KirrR mutations of EF-Tu alone ( Figure 5) cause an error-prone phenotype.…”
Section: Interactions With Ef-tu and The 50s Subunitmentioning
confidence: 99%
“…Further, the G2661C/S12-SmP double mutant can be rescued not only by Smmediated reinforcement at the shoulder, but also by certain kirromycin-resistant (KirrR) mutants of EF-Tu (173). These KirrR mutations of EF-Tu alone ( Figure 5) cause an error-prone phenotype.…”
Section: Interactions With Ef-tu and The 50s Subunitmentioning
confidence: 99%
“…Recently, a G --C mutation at position 2661 in the a-sarcin loop has been shown to impair translational elongation, but, surprisingly, only in combination with restrictive streptomycin-resistance mutations in protein S12 (40). The functional impairment of this double mutant is suppressed by a third mutation, in EF-Tu itself (41). Furthermore, it has been observed that the normally recessive kirromycin resistance caused by mutations in EF-Tu becomes dominant in certain restrictive S12 mutant backgrounds (42).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotides at the sarcin domain are involved in elongation factors catalyzing the binding of aminoacyltRNA to ribosomes [34]. These nucleotides may be involved in factors catalyzing the translocation, because treatment of ·-sarcin aborts these reactions [28,34].…”
Section: Introductionmentioning
confidence: 99%
“…These nucleotides may be involved in factors catalyzing the translocation, because treatment of ·-sarcin aborts these reactions [28,34]. Aminoacyl-tRNA, peptidyl-tRNA, or both have been shown to be bound to the ribosome and to protect against the treatment of ·-sarcin [22,25,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation